ANALISIS PERSEPSI TENTANG KETERAMPILAN KOLABORATIF PESERTA DIDIK TERHADAP PEMBELAJARAN BIOLOGI DI SMA NEGERI 1 PADANG - Nilam Sari, Puteri; Fadilah, Muhyiatul (Jurnal Biogenerasi, 2025)
This research aims to analyze students' perceptions of collaboration skills regarding biology learning at SMA Negeri 1 Padang. The research was carried out using quantitative descriptive methods. The research population is students with a sample of 213 students selected using total sampling techniques. Data collection was carried out through questionnaires and direct observation, with research instruments that have been validated and show high reliability (Cronbach's Alpha = 0.85). The research results show that students' collaboration skills are in the very good category with an average percentage of 81.04%. Analysis of five indicators of collaboration skills produced the following findings: (1) conflict resolution obtained the highest percentage of 82.12%, indicating excellent ability in managing differences of opinion; (2) project management reached 81.69%, indicating excellent ability in organizing learning tasks; (3) tolerance reached 81.43%, reflecting excellent mutual respect; (4) group interaction of 80.53%, indicating good communication skills; and (5) contribution to the team was 79.44%, indicating a good willingness to contribute to achieving common goals. This research concludes that biology learning has succeeded in facilitating the development of students' collaboration skills. The implications of this research are the need to optimize learning strategies that can further increase the contribution of students in teams, as well as the importance of maintaining achievements in other indicators through a variety of appropriate learning activities.